IMPACT OF COVID-19 ON SHARE PRICE VOLATILITY: A LITERATURE STUDY - Audina Rahmi (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2021)
The COVID-19 pandemic has had a huge impact on economies around the world, especially on the volatility of stock prices. This study aims to examine the literature related to changes in the stock market during the COVID-19 pandemic, and to synthesize the insights that have emerged from a large number of studies. The results of the study conclude a number of factors due to COVID-19 that cause stock price volatility